Pelatihan Computer Assisted Test dalam Rangka Menghadapi Tes CPNS 2021 di Kota Pontianak - Sulaiman, Sulaiman; Radiansah, Dody (Kapuas, 2022)
In 2021, the CPNS acceptance will again be carried out by the government. As a profession that is favored by the community, careful preparation of course needs to be done in various ways, one of which is by participating in problem-solving training activities and debriefing from the presenters. In this activity, the presenters are experienced experts so they are expected to motivate participants and foster enthusiasm in the face of CPNS acceptance later. In this Community Service participants will get tricks in facing the test and perform a simulation of working on CAT questions that have been prepared and then evaluate the results of the simulation work.